THE ESTIMATION OF ADAPTABILITY PARAMETERS OF THE COLLECTION SAMPLES OF SAINFOIN - S. A. Ignatiev; A. A. Regidin (Зерновое хозяйство России, 2019)
The estimation of the initial material is the most important part of the breeding process. There is a great necessity in additional objectivity of its characteristics, in identification of the parameters of environmental adaptability, stability, resistance to stressful environmental conditions. Within the collection nursery there have been studied adaptability parameters of 16 sainfoin samples (Onobrychis arenaria Kit. DC) of a sandy species. The purpose of research was to identify sainfoin forms with a complex of adaptive traits based on such characteristics as “green mass productivity” and “seed productivity” to use them in future breeding work. There have been used conventional techniques in the study. The estimation of the adaptability parameters was carried out according to Eberhart S.G., Russell W.G. (1966) presented by V.A. Zykina et al. (2005) and by V.Z. Pakudin (1984). The conducted dispersion analysis of the two-factor trial on the productivity of sainfoin samples showed the correlation between the genotype and the environment. The change in green mass and seed productivity was greatly influenced by the factor ‘year’ (‘environment’) (51% and 58%, respectively). The influence of the factor ‘variety’ (‘sample’) was less (40.7% and 35.5%), the correlation of these factors was also reliable, the interaction variance exceeded the error value and was 65% and 79%. The estimation of sainfoin samples for the presence of adaptive properties revealed that almost all the studied samples had at least one adaptive parameter. But, the sainfoin samples that have several or a set of calculated adaptive properties are obviously more valuable for the use in the breeding process. When cultivating for green mass and seeds, the samples ‘S 5/05’ and ‘GIA 4’ had a high level of resistance to stressful growing conditions (Umin-Umax), a high level of environmental adaptability (bi) and stability (Si2 ), and the samples ‘GIA 2’ and ‘GIA 11’ have these parameters only if they are cultivated for green mass. The variety ‘Severokavkazsky Dvuukosny’ is characterized with high resistance to stressful growing conditions (Umin-Umax) and genetic flexibility ((Umin + Umax) / 2), with a high level of ecological adaptability (bi) and homeostatism (HOM).